Diurnal variation of turbulence-related quantities in Lake Garda - W.K. Lenstra (Advances in Oceanography and Limnology, 2014)
To determine diurnal variations in the physical and biological state of Lake Garda in early spring, high-resolution measurements were made of the vertical distribution of temperature and fluorescence in the upper 100 meters during 5–7 March 2014. In this paper, the results of these measurements are presented and a preliminary analysis that focuses on the connection between the vertical mixing coefficient KT and the chlorophyll-a (chl-a) concentration is given. From these first direct measurements of turbulence-related quantities in Lake Garda, it is found that mixed-layer values of KT decrease, while surface chl-a concentrations increase, over the day. Variations in KT can be connected to the changes in the surface wind stress, while variations in chl-a are negatively correlated with the amplitude of KT. In addition, satellite observations of the surface chl-a concentration are analysed to test their use for the calibration of the fluorescence measurements and also for their potential utility in remotely determining vertical mixing in the upper layers of the lake.